Como os cágados sobrevivem e se reproduzem na caatinga? Aspectos da história de vida de Phrynops tuberosus (Testudines: Chelidae) - Rodrigues, João Fabrício Mota (2013)
The life history theory studies the characteristics combinations that maximize the organisms reproduction and survival in the environment where they live. The species use the habitat in a diverse way and this use depends on the environmental conditions in the available habitats. Phrynops tuberosus, a freshwater turtle found in the north-northeastern regions of Brazil, is the animal-model chosen for the life history traits and habitat use studies. This work aims understand how this species reproduce, maintain and use the habitat in Caatinga. The study generated biological and ecological knowledge of the species and allowed the testing of hypotheses and predictions of life history traits, sexual dimorphism and habitat use. Selection of clutching sites, males smaller than females and preference of larger animals for environments most exposed were found in the populations studied. The results facilitate understanding of reproduction and survival of turtles in a semiarid environment.